VEGETASI ALAMI DAN PERUBAHANNYA SETELAH 22 TAHUN (1986 - 2008) DI HUTAN TANAMAN Altingia excelsa Noronha CANDIKUNING-BALI - Siregar, Mustaid; Undaharta, Ni Kadek Erosi (BERITA BIOLOGI, 2014)
Research at the three locations of Altingia excelsa Noronha plantations in Candikuning, Bali has been carried out to examine the changes in vegetation that grows naturally in the low layer after 22 years (1986 -2008). The results showed that 40 species of seedling, and 4 species of shrubs and young trees were found in three plots of the plantation forest. Compared to the results of the previous study, 22 years before the present study (1986), species richness was decreased dramatically accompanied by changes in species composition. Crown cover of herbs group were decreased, but shrubs and young trees were increased except for the plot 1938 due to edge effects. Lightdemanding species were disappeared and replaced by shaded-tolerant species. The primary tree species which are commonly found in the surrounding natural forest and previously found in research plots had been disappeared, and replaced by late secondary tree species, and seedlings of A. excelsa which is actually animmigrant species. Succession under the plantation forest of A. excelsa are generally slow.